Experimental Study on Development of Mooring Simulator for Multi Floating Cranes - Junhyeok Bae; Juhwan Cha; Min-Guk Seo; Kangsu Lee; Jaeyong Lee; Namkug Ku (Journal of Marine Science and Engineering, 2021)
In this study, the coupled motion of a mooring system and multifloating cranes were analyzed. For the motion analysis, the combined equations of motions of the mooring line and multifloating cranes were introduced. The multibody equations for floating cranes were derived from the equations of motion. The finite element method (FEM) was used to derive equations to solve the stretchable catenary problem of the mooring line. To verify the function of mooring simulator, calculation results were compared with commercial mooring software. To validate the analysis results, we conducted an experimental test for offshore operation using two floating crane models scaled to 1:40. Two floating crane models and a pile model were established for operation of uprighting flare towers. During the model test, the motion of the floating cranes and tensions of the mooring lines were measured. Through the model test, the accuracy of the mooring analysis program developed in this study was verified. Therefore, if this mooring analysis program is used, it will be possible to perform a mooring analysis simulation at the same time as a maritime work simulation.